2004
DOI: 10.1097/01.tp.0000137936.75203.b4
|View full text |Cite
|
Sign up to set email alerts
|

Superior Survival and Proliferation after Transplantation of Myoblasts Obtained from Adult Mice Compared with Neonatal Mice

Abstract: Myoblasts derived from neonatal mice were inferior for transplantation, and early passage donor myoblasts from adult mice are recommended for MTT in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Myoblasts isolation and purification rendered them largely incapable of proliferation and fusion in recipient environment: probably the isolation procedure produced subtle changes in the myoblasts that rendered them either more visible to the host immune system or less viable for fusion in vivo [27]. Interestingly, Lee-Pullen et al studied the transplantation efficiency of myoblasts isolated from both adult and neonatal mice [28]. The majority of MTT used donor myoblasts from neonate tissue on the basis of increased yield of activated precursor cells at this young age.…”
Section: Myoblastsmentioning
confidence: 97%
See 1 more Smart Citation
“…Myoblasts isolation and purification rendered them largely incapable of proliferation and fusion in recipient environment: probably the isolation procedure produced subtle changes in the myoblasts that rendered them either more visible to the host immune system or less viable for fusion in vivo [27]. Interestingly, Lee-Pullen et al studied the transplantation efficiency of myoblasts isolated from both adult and neonatal mice [28]. The majority of MTT used donor myoblasts from neonate tissue on the basis of increased yield of activated precursor cells at this young age.…”
Section: Myoblastsmentioning
confidence: 97%
“…Other groups isolated donor myoblasts from more mature muscle at a time when the myoblasts are quiescent, as they are closer to the source of donor cells from adult tissues used in clinical studies. As they demonstrated that adult myoblasts showed sustained survival and striking proliferation in comparison with neonate-derived myoblasts, it became clear that the source of donor myoblasts could have a pronounced effect on the efficacy of the procedure [28]. Moreover, problems regarding inadequate immunosuppression arose.…”
Section: Myoblastsmentioning
confidence: 98%
“…However, another study reported only a slight difference between the numbers of dystrophin positive fibres after injection of late pre-plate (PP6), or early passage primary myoblasts, although it should be noted that the MDSC were injected after many passages in vitro (29). We have recently observed increased survival and also proliferation in a population of late pre-plate cells (equivalent to MDSC) extracted from adult mice (30). Following an initial loss of 50% of male donor cells by 24 h, no further decrease was observed for up to 3 weeks post-transplantation.…”
Section: Muscle-derived Stem Cellsmentioning
confidence: 99%
“…A number of studies have examined transplantations of normal stem cells such as hematopoietic stem cells (HSCs1), myoblasts, and stem cells derived from other tissue types as possible treatments for DMD and as a gene delivery system for therapeutic recombinant proteins (Camargo et al 2003; Huard et al 2003; Lee-Pullen et al 2004; Parker et al 2008; Partridge et al 1998; Torrente et al 2004). The disease phenotype of the mdx mouse model also shows improvement after the injection, either intramuscular or intravenous (Gregorevic et al 2004; Gregorevic and Chamberlain 2003; Liu et al 2005), of viral vectors encoding full-length or truncated but functional dystrophins (DelloRusso et al 2002; Dudley et al 2004; Harper et al 2002b).…”
Section: Treatmentsmentioning
confidence: 99%
“…Fusion of mononucleated myoblasts either into multinucleated muscle fibers or with existing myofibers is a normal part of muscle repair. Normal myoblasts are able to fuse with dystrophic myoblasts to form myotubes that express dystrophin in vitro (Huard et al 2003; Lee-Pullen et al 2004). Similarly, intramuscular injection of myoblasts from normal donor mice reconstituted muscle fibers and led to dystrophin expression in mdx mice despite the rapid death of a high percentage of donor cells (Beauchamp et al 1999; Jejurikar and Kuzon 2003; Lee-Pullen et al 2004; Skuk et al 2004).…”
Section: Treatmentsmentioning
confidence: 99%